1994
DOI: 10.3109/02713689408999874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endothelin-1 on intraocular pressure and aqueous humor dynamics in the rabbit eye

Abstract: The effects of endothelin-1 (ET-1) on intraocular pressure (IOP) and aqueous humor dynamics were studied in the rabbit eye. The intravitreal injection of 10(-5) M ET-1 (20 microliters) produced a biphasic IOP response consisting of an initial rise of 1 to 2 hours in duration, and a subsequent prolonged reduction lasting for more than 96 hours. Aqueous humor dynamics were determined 24 hours after the 10(-5) M ET-1 injection. Aqueous humor formation, measured fluorophotometrically, was decreased by 58%. Total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
44
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 13 publications
4
44
1
Order By: Relevance
“…The suppression of aqueous humor flow previously reported in rabbits (Taniguchi et al 1994) also was not observed in our monkeys. These negative results are reported here.…”
supporting
confidence: 65%
See 4 more Smart Citations
“…The suppression of aqueous humor flow previously reported in rabbits (Taniguchi et al 1994) also was not observed in our monkeys. These negative results are reported here.…”
supporting
confidence: 65%
“…There was a small but significant bilateral increase at the 1 mM dose (treated/BLΩ1.19∫0.05, p∞0.01; control/ BLΩ1.27∫0.10, p∞0.05) but no difference between the eyes (Trt/ContΩ 1.00∫0.09; Trt/BL vs Cont/BLΩ 0.95∫0.05). An increase in AHF would not be expected based on the aqueous flow reduction reported in rabbits (Taniguchi et al 1994). …”
Section: Aqueous Humor Flowmentioning
confidence: 94%
See 3 more Smart Citations